Pemetaan Sistem Informasi Infrastruktur Transportrasi Di Kabupaten Ketapang - Azwansyah, Heri; Juniardi, Ferry (ELKHA: Jurnal Teknik Elektro, 2014)
Abstract Database available transport infrastructure is the basis for developing transportation. This study is an effort to map the existing conditions in the transport infrastrutkur Ketapang. This study requires data transport infrastructure of land communications obtained from relevant agencies and field surveys. This study resulted in Transport Infrastructure Database in Ketapang that can be implemented with web GIS applications. These results may provide transportation infrastructure mapping information spread across Ketapang KeywordsDatabase, Transport Infrastructure, Web GIS